2021
DOI: 10.1001/jamanetworkopen.2021.4475
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Pediatric Admissions for Kawasaki Disease or Infectious Disease During the COVID-19 State of Emergency in Japan

Abstract: IMPORTANCEThe development of Kawasaki disease (KD) has been suggested to be associated with droplet-or contact-transmitted infection; however, its triggers and transmission modes remain to be determined. Under an epidemic of SARS-CoV-2, the COVID-19 state of emergency in Japan served as a nationwide social experiment to investigate the impact of quarantine or isolation on the incidence of KD.OBJECTIVE To assess the role of droplet or contact transmission in the etiopathogenesis of KD. DESIGN, SETTING, AND PART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 52 publications
2
42
0
2
Order By: Relevance
“…Thus, the reduced transmission of microbes other than SARS‐CoV‐2 may explain the observed decreased incidence of Kawasaki disease in the present study. Our finding was in line with a study from six hospitals in Japan, which showed a possible 27% reduction in Kawasaki disease, with an incidence rate ratio of 0.73 (95% CI: 0.48‐1.10) during the COVID‐19 pandemic 21 . The aetiopathogenesis of Kawasaki disease has been extensively studied but is not fully understood.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the reduced transmission of microbes other than SARS‐CoV‐2 may explain the observed decreased incidence of Kawasaki disease in the present study. Our finding was in line with a study from six hospitals in Japan, which showed a possible 27% reduction in Kawasaki disease, with an incidence rate ratio of 0.73 (95% CI: 0.48‐1.10) during the COVID‐19 pandemic 21 . The aetiopathogenesis of Kawasaki disease has been extensively studied but is not fully understood.…”
Section: Discussionsupporting
confidence: 90%
“…The existence of these sub-phenotypes suggests that Kawasaki disease might be triggered by diverse agents that each yield slight variations in clinical presentation 98 . A surprising observation from the past year is the large decrease in the incidence of Kawasaki disease in Japan and the USA during the SARS-CoV-2 pandemic, which supports the hypothesis that Kawasaki disease is triggered by inhaled aerosols that can be blocked or reduced by the use of facial masking 99 , 100 . The possibility of long-range transport of aerosols linked to fluctuations in Kawasaki disease incidence has been studied in both Northern and Southern Hemispheres 93 , 101 , 102 .…”
Section: Medium Vessel Vasculitismentioning
confidence: 69%
“…In other countries where COVID-19 infection rates are similarly low, such as Japan, South Korea, and Finland (cumulative COVID-19 incidence rates of 1363.841, 762.093, and 3231.09 per 100,000 people, respectively) [ 6 ], KD incidence rates declined following the implementation of public health measures in 2020. In Japan, where a state of emergency was declared from 7 April–25 May 2020, and school closures were enacted between 2 March–31 May 2020, incidence rates of KD began to decline beginning in March in 11 hospitals in the Yamanashi prefecture [ 14 ], in April in 18 hospitals in the Kobe area [ 15 ], and in June in six hospitals in Fukuoka [ 16 ]. In both Finland and South Korea, KD incidence rates declined after the implementation of school closures.…”
Section: Discussionmentioning
confidence: 99%